TEACHER READINES AND CHALLENGES IN IMPLEMENTATION OF MERDEKA CURRICULUM IN MADRASAH IBTIDAIYAH - Mulabbiyah Mulabbiyah; Rohaya Sulong (Universitas Islam Negeri Mataram, 2024)
Teachers are one of the spearheads of implementing the curriculum at school. With the implementation of the Merdeka Curriculum, it is important to know the readiness of teachers in implementing it and the challenges they face. This study aims to describe teachers' readiness to implement the Merdeka Curriculum in Madrasah Ibtidaiyah Mataram City and identify the challenges faced. This research is a phenomenological qualitative research. Data were collected through interviews, observation and documentation. Furthermore, the data is analyzed interactively through the stages of data reduction, data presentation and conclusion drawing. Data validity testing was carried out by increasing diligence, triangulation of sources and triangulation of methods. The results showed that the teacher's readiness to implement the Merdeka Curriculum in MI Mataram City was quite good, it just needed to be improved. Various challenges faced by teachers in implementing the Merdeka Curriculum include (1) teachers do not fully understand and are able to develop Merdeka Curriculum learning tools, (2) it takes a long time to be able to compile all learning tools, especially teaching modules and project modules to strengthen the Pancasila Student Profile, (3) lack of supporting infrastructure, (4) large number of students for each rombel, (5) inadequate classroom size for differentiated learning, (6) lack of cooperation and parental involvement, (7) teachers have difficulty carrying out diagnostic assessments and preparing varied/different questions for formative assessments and summative assessments according to student learning needs.